1995
DOI: 10.1002/cpp.5640020406
|View full text |Cite
|
Sign up to set email alerts
|

Does the health belief model predict risky sexual practices in injection drug users?

Abstract: The current research assessed Health Belief Model (HBM) constructs, sexual behaviour, and drug use practices in 123 heterosexual IDUs (62 men and 61 women) who were seronegative for HIV. Results indicated that HBM variables significantly explained 25% of the variance in condom usage in IDU men. Higher reports of condom usage were associated with negative attitudes related to condom discomfort, inconvenience, and acceptance; positive attitudes related to perceptions of condoms as adding excitement to sex; posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…This finding is consistent with many studies in the literature that have found that alcohol abuse and illicit drug abuse are independently associated with high risk sexual behavior, and the risk for HIV transmission [45,54]. Substance abusing individuals may engage in higher risk sexual behavior because of impaired decisionmaking while under the influence of substances [10], as well as be more likely to have higher risk sexual partners [6,29].…”
Section: Discussionsupporting
confidence: 91%
“…This finding is consistent with many studies in the literature that have found that alcohol abuse and illicit drug abuse are independently associated with high risk sexual behavior, and the risk for HIV transmission [45,54]. Substance abusing individuals may engage in higher risk sexual behavior because of impaired decisionmaking while under the influence of substances [10], as well as be more likely to have higher risk sexual partners [6,29].…”
Section: Discussionsupporting
confidence: 91%
“…When measured at a single point in time, both perceived norms for safe sex and attitudes toward safe sex were significantly associated with unprotected anal intercourse. The observed correlations between attitudes, norms, and unprotected sex are consistent with a large body of cross-sectional research on both sexual risk (e.g., Ayoola et al, 2007;Boone & Lefkowitz, 2004;Denny-Smith et al, 2006;Downing-Matibag & Geisinger, 2009;Lin et al, 2005;Lollis et al, 1995;Pearson, 2006;Ragsdale et al, 2007;Rhodes & Hergenrather, 2003;Robinson et al, 2005;Steers et al, 1996) and other health behaviors (e.g., Aiken, West, Woodward, & Reno, 1994;Kiviniemi, Voss-Humke, & Seifert, 2007;Lindley, Wortley, Winston, & Bardenheier, 2006;McClenahan, Shevlin, Adamson, Bennett, & O'Neill, 2007). However, in contrast to the causal predictions made by most theories of health behavior, attitudes and norms did not predict sexual risk behavior over time.…”
Section: Discussionsupporting
confidence: 83%
“…Since the discovery of HIV more than two decades ago, behavioral scientists have sought to apply health behavior theories to understanding individuals’ HIV-related sexual risk behaviors (for a review, see, Fisher & Fisher, 2000). During this time abundant cross-sectional research has been conducted which shows associations between sexual risk behavior and assorted attitudes and beliefs (e.g., Ayoola, Nettleman, & Brewer, 2007; Boone & Lefkowitz, 2004; Denny-Smith, Bairan, & Page, 2006; Downing-Matibag & Geisinger, 2009; Lin, Simoni, & Zemon, 2005; Lollis, Antoni, Johnson, Chitwood, & Griffin, 1995; Pearson, 2006; Ragsdale, Anders, & Philippakos, 2007; Rhodes & Hergenrather, 2003; Robinson, Scheltema, & Cherry, 2005; Steers, Elliott, Nemiro, Ditman, & Oskamp, 1996). …”
Section: Introductionmentioning
confidence: 99%
“…For example, McCarthy et al (1996) found that difficulty in keeping medical appointments and transportation problems were better predictors of mammography screening attendance than the components of the health belief model. Lollis, Antoni, Johnson, Chitwood, and Griffin (1995) found that condom usage was predicted by drug use, condom discomfort, inconvenience, and acceptance of condoms, in addition to components related to perceived health threat. Beck (1981) asked participants how often in the previous 6 weeks they had driven a car while they were drunk or while they knew that they had had too much to drink.…”
Section: Discussionmentioning
confidence: 98%
“…One possibility is that in many studies in the past, the focus of the study was on the health threat and factors that might prevent the heath threat, with much less attention being paid to other factors. When alternative variables have been included, they can outweigh the health threat (Goldberg et al, 2002; Lollis et al, 1995; McCarthy et al, 1996; Parsons et al, 1997). Overall, the results suggest that there are both theoretical and practical implications.…”
Section: Discussionmentioning
confidence: 99%